Discriminaties bestrijden of diversiteit op de arbeidsmarkt promoten? Overzicht van een overheidsoptreden in het Brussels Hoofdstedelijk Gewest (1997-2012) - Alexandre Tandé (Brussels Studies, 2018)
At the end of the 1990s, the Brussels-Capital Region launched actions to fight against employment discrimination with respect to people of foreign origin. In a social and historical perspective, using oral and documentary sources, this article presents the context in which this public policy emerged, the experimental actions in the first years, and its transformation in the mid 2000s. At the same time that it was consolidated (inclusion of new measures in the regional law, establishment of a Brussels unit of consultants in the area of diversity), this policy was also given a new objective: the promotion of diversity. While the fight against discrimination and the promotion of diversity are often presented as the "two sides of the same coin", these two objectives may also diverge or oppose each other. A review of the history of this Brussels policy, its evolution and impact, therefore allows the current responses to two major challenges for the urban area to be questioned: the inequality of access to employment and the recognition of sociocultural diversity.